Vocational Education and Training in Sub-Saharan Africa Current Situation and Development - Eicker, Friedhelm (W. Bertelsmann Verlag, 2017)
There is a rising demand for specialist workers in several countries of Sub-Saharan Africa (SSA). The area still lacks a consistent system of professional training and further education. The conference transcript comprises practical knowledge collected by the authors to depict the current state of professional training within the Sub-Saharan African countries. The paper also introduces the reader to concepts for the development of a professional training system and provides an overview of the strategies and plans of different countries and institutions. The included articles were written within the framework of a symposium on the status quo and the perspective of professional training and further education. This gathering took place in Namibia in August 2016 and brought together researchers and business actors from the Sub-Saharan states, Europe, Australia, and Asia.